CURRENT ASPECTS OF NOSOCOMIAL LEGIONELLOSIS PROFILAXIS - I. S. Tartakovsky; O. A. Grusdeva; N. I. Gabrielyan (Вестник трансплантологии и искусственных органов, 2010)
The nosocomial or hospital acquired infections is one of the most important medical and social problem. Mo- dern strategy of nosocomial infections prevention include prevention of nosocomial legionellosis. Epidemic outbreaks of nosocomial legionellosis with high mortality rate (20–40%) were recognized last years in different countries. The contaminated by Legionella hospital hot water supply system is a source of Legionella infection outbreaks. A risk reduction strategy of waterborne pathogens in hospital water system is important part of mo- dern conception of nosocomial infection prevention, especially among immune compromised patient including transplant patients. In revue discussed different aspects of epidemiology, laboratory diagnostic and prevention of nosocomial legionellosis.